A 'possibilist' approach to regional banking systems and financial integration: The Italian experience - Pietro Alessandrini; Alberto Zazzaro (European Regional Science Association (ERSA), 1998)
Over the last ten years there have been great strides made in the analysis of the regional structure of banking systems and financial integration both from the theoretical and empirical point of view. Experience shows that the financial structure tends to be hierarchical with an advanced financial centre at the top and local credit systems becoming gradually less advanced depending on the peripheral regions in which they operate. It is essential to recognise and deal with this fact and to consider the question of financial integration between the global and the local or, to be more exact, between the centre and the periphery. There are three basic ways to approach this question. The first two approaches present two well-known opposite views concerning the effects of integration: one is pessimistic and the other optimistic. In our opinion a third point of view, which we will call "possibilist", falls midway between the two extremes and offers a more realistic and accurate picture of the situation. The first two theories, widely discussed in the literature, have certain points in common. In particular, both emphasise a strong contrast between centre and periphery and attempt to ignore one of the two poles in the conviction that the other will prevail.The pessimistic theory concentrates exclusively on "localism". It maintains that the centre would take advantage of asymmetries in information, behaviour and structure and would invest the savings drained out of the peripheral regions and in this way slow down their development. This could lead to the radical conclusions that local segmentation of capital markets is preferable to integration. The optimistic theory concentrates exclusively on "globalisation". The hope is that higher competition will select the best enterprises (banks, firms) and standardise their performance at the levels of efficiency reached in the more advanced centre. This opinion leads one to believe that every region can become a centre in the hope of exorcising its peripheral nature. In our opinion, it is wiser to adopt what we call a "possibilist" or "open" approach. It is based on the continual exploration of the possibility of co-existence, complementarity, and interaction between different areas and therefore also between the centre and periphery. The territorial integration of local financial systems, which should not be disputed, must be carried out in a selective and gradual way, by trying to give preference to solutions that are best suited to the characteristics and assimilation ability of local firms and individuals. The paper deal with these questions by focusing our attention on the experience of the Italian banking system.
Keywords: 330